Evaluasi Pengembangan Desa Wisata Kerta Kecamatan Payangan, Kabupaten Gianyar - I Putu Adi Suardika (Universitas Warmadewa, 2020)
The issuance of Law No. 6 of 2014 about villages make villages have autonomy to regulate and run their own government, and this is followed by a series of funding received by the village. Villages are required to use village funds for productive economic development according to their potential. In line with this policy, in 2017 the Gianyar Regency Government established 9 tourist villages. One of them is Kerta Village, which is developing new rural-based tourist destinations. This study aims to evaluate the development of a tourist village in Kerta Village and the strategies that can be taken in developing a tourist village. Data collection was carried out by field studies, namely observation techniques, in-depth interviews, and documentation studies. The data analysis used a qualitative descriptive method. The results of the study found that the development of the Kerta tourism village was not optimal. Even though Kerta Village has been able to realize new tourist village destinations, its development has not been effective and efficient. The development strategy that must be carried out in order to become a developed rural tourism destination is to develop integrated tourism in a collaborative / partnership manner, increase promotion, highlight uniqueness, and build an image.